2012
DOI: 10.1371/journal.pone.0040145
|View full text |Cite
|
Sign up to set email alerts
|

A Pro-Cathepsin L Mutant Is a Luminal Substrate for Endoplasmic-Reticulum-Associated Degradation in C. elegans

Abstract: Endoplasmic-reticulum associated degradation (ERAD) is a major cellular misfolded protein disposal pathway that is well conserved from yeast to mammals. In yeast, a mutant of carboxypeptidase Y (CPY*) was found to be a luminal ER substrate and has served as a useful marker to help identify modifiers of the ERAD pathway. Due to its ease of genetic manipulation and the ability to conduct a genome wide screen for modifiers of molecular pathways, C. elegans has become one of the preferred metazoans for studying ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 53 publications
(69 reference statements)
3
39
0
Order By: Relevance
“…3E ). In support of these observations, 35 S-methionine/cysteine labeling showed that basal-B lines (Hs578T, BT549, MDA-MB-157, SUM159, MDA-MB-231, and 4T1) also exhibited, on average, a more than 40-fold increase in protein secretion relative to luminal lines (MCF7, T47D, BT474, and ZR-75-3; Fig. 3F ).…”
Section: Cells That Undergo An Emt Are Highly Secretorysupporting
confidence: 68%
See 2 more Smart Citations
“…3E ). In support of these observations, 35 S-methionine/cysteine labeling showed that basal-B lines (Hs578T, BT549, MDA-MB-157, SUM159, MDA-MB-231, and 4T1) also exhibited, on average, a more than 40-fold increase in protein secretion relative to luminal lines (MCF7, T47D, BT474, and ZR-75-3; Fig. 3F ).…”
Section: Cells That Undergo An Emt Are Highly Secretorysupporting
confidence: 68%
“…Relative expression To determine whether increased ECM secretion is a general feature of EMT, we examined the expression of ECM genes identifi ed to be upregulated upon EMT ( Fig. 3A ) in basal-B and luminal breast cancer lines ( 35 ). Basal-B cancer lines ( n = 9) expressed many EMT ECM genes-including FN1 , COL1A1 , COL1A2 , COL4A1 , COL5A1 , POSTN , FBN1 , and COL6A1 -at signifi cantly higher levels than luminal breast cancer lines ( n = 13; Fig.…”
Section: Cells That Undergo An Emt Are Highly Secretorymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently the amount of aggregates in the head region of 10 worms was counted. As a control for efficient inhibition of the autophagy pathway, autophagosome formation of nhx-2:: mCherry::lgg-1; myo-2::GFP worms was visualized upon RNAi treatment following 4 hr starvation as previously described (Miedel et al 2012).…”
Section: Autophagymentioning
confidence: 99%
“…Since depletion of mdt-15 had no effect on the degree of SRP-2 H302R ::YFP aggregation, they conclude that this mutation activates the UPR directly by altering ER membrane lipid content and not secondarily by impairing protein folding capability within the ER and stimulating the UPR by increasing the accumulation of misfolded species. Further, evidence for this direct effect is supported by no increase in a second ER folding sensor, the luminal ERAD substrate, CPL-1 W32A,Y35A :: YFP (Miedel et al 2012;Hou et al 2014). While the overall conclusions of this study are supported by the CPL-1 misfolding mutant, we are hesitant to draw this conclusion based on the experiments using SRP-2 H302R ::YFP per se.…”
Section: Discussionmentioning
confidence: 61%